Analisis Kemampuan Berpikir Tingkat Tinggi Dalam Menyelesaikan Masalah Open Ended Pada Materi Sistem Persamaan Linear Dua Variabel - Rini Andriani; Muh. Turmuzi; Wahidaturrahmi; Sudi Prayitno (Griya Journal of Mathematics Education and Application, 2022)
This study aims to describe higher order thinking skills in solving open ended problems on the material of a two variable linear equation system for class IX students of SMP Negeri 5 Mataram in the 2021/2022 academic year. The Indicators of higher thinking skills consist of analyzing, evaluating, and creating. This type of research is a mixed methods. Mixed method research was research that combines qualitative and quantitative research.The data of this research were collected through observation, tests, interviews and documentation. The subjects of this research was used purposive sampling method. The data collection with the test method was carried out on 20 subjects. Data collection by interview method was conducted by selecting 6 students based on the results of the higher order thinking skill ability test, namely 2 students in the high category, 2 students in the medium category and 2 students in the low category. The results showed that 15% of students had higher order thinking skills in the high category with an average score of 77.67, 45% of students in the medium category with an average score of 62.97 and 40% of students in the low category with an average score. average 26.48. The students' higher order thinking ability is in the low category with an average value of 50.58. The achievement of analyzing indicators is 60%, evaluating indicators is 47% and indicators creating 47.5%.